Neutral‐point clamped n‐level multilevel converter without dead time and shoot‐through problem. Issue 15 (1st July 2017) - Lee, E.‐C.; Choi, N.‐S.; Kim, H.‐J.
Abstract : A generalised n ‐level multilevel converter that has no shoot‐through problem and thus is operated without dead time at each commutation is proposed. It is obtained by modifying the traditional neutral‐point clamped multilevel converter topology based on dual‐buck converter concept. The m ‐phase n ‐level converter can be readily constructed by using the proposed multilevel converter topology. The half‐bridge five‐level inverter, as an example case, is presented along with the operating principle and modulation and control methods. Experimental results show the feasibility and validity of the proposed converter.